Protective Role of the Podocyte IL-15 / STAT5 Pathway in Focal Segmental Glomerulosclerosis - Aïssata Niasse; Kevin Louis; Olivia Lenoir; Chloé Schwarz; Xiaoli Xu; Aymeric Couturier; Hélène Dobosziewicz; Anthony Corchia; Sandrine Placier; Sophie Vandermeersch; Lothar Hennighausen; Perrine Frère; et al. (Kidney International Reports)
Introduction: During glomerular diseases, podocyte-specific pathways can modulate the intensity of histological disease and prognosis. The therapeutic targeting of these pathways could thus improve the management and prognosis of kidney diseases. The Janus Kinase/Signal Transducer and Activator of Transcription (JAK/STAT) pathway, classically described in immune cells, has been recently described in detail in intrinsic kidney cells. Methods: We describe STAT5 expression in human kidney biopsies from patients with focal segmental glomerulosclerosis (FSGS) and studied mice with a podocyte-specific Stat5 deletion in experimental glomerular diseases. Results: Here, we show, for the first time, that STAT5 is activated in human podocytes in FSGS. In addition, podocyte-specific Stat5 inactivation aggravates the structural and functional alterations in a mouse model of FSGS. This could be due, at least in part, to an inhibition of autophagic flux. Finally, interleukin 15 (IL-15), a classical activator of STAT5 in immune cells, increases STAT5 phosphorylation in human podocytes, and its administration alleviates glomerular injury in vivo by maintaining autophagic flux in podocytes. Conclusion: Activating podocyte STAT5 with commercially available IL-15 represents a potential new therapeutic avenue for FSGS.